Crime Victims, Immigrants And Social Welfare: Creating The Racialized Other In Sweden - Branteryd, Fia (The British journal of criminology, 2022)
This study explores the role of immigration and racialization in creating the first Swedish victim support centre in the early 1980s. The study is based on a qualitative content analysis of the archives of Victim Support Södertälje, the first lasting Swedish victim support centre, from 1983 to 1990. While many of the centre’s activities focused on crime prevention, it defined crime and victimization as the province of immigrant communities in Södertälje, and, notably, as outside—and aberrant from—the imagined racial community of Sweden. Thus, victim support centres were one of the mechanisms to continue to defend the ideals of the Swedish welfare state, but to do so in ways that prevented incursions within Swedish racial homogeneity from the outside.